2012
DOI: 10.4236/wsn.2012.41004
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Sensor Network Solution for Precision Agriculture Based on Zigbee Technology

Abstract: The article has been retracted due to the investigation of complaints received against it. The Editorial Board found that substantial portions of the text quite like the one published in other journal. The problem is under investigation. This paper published in Vol.4 No.1, 2012, has been removed from this site temporally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 10 publications
0
51
0
2
Order By: Relevance
“…Thus, the WSN is most suitable for collection of information spread over wide area. On intensive study, it is found that, the WSN is significantly used for precision agriculture [7], wherein, the parameters of spatio-temporal variations should be essentially monitored. The WSN also proved its suitability for monitoring transportation, environmental monitoring, forecasting, pollution monitoring, security, disaster management etc [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the WSN is most suitable for collection of information spread over wide area. On intensive study, it is found that, the WSN is significantly used for precision agriculture [7], wherein, the parameters of spatio-temporal variations should be essentially monitored. The WSN also proved its suitability for monitoring transportation, environmental monitoring, forecasting, pollution monitoring, security, disaster management etc [8].…”
Section: Introductionmentioning
confidence: 99%
“…The IEEE 802.15.4 based ZigBee (ZigBee Alliance, 2004) and a ZigBee-like propriety networking protocol, XMesh (Crossbow, 2007a), among others, ported to some of the node hardware platforms, have made significant impact on a broad range of applications. Over a few years, many applications of WSN have appeared in areas such as building automation (ZigBee Alliance, 2006), (Kazmi et al, 2014), health care (ZigBee Alliance, 2008), defense and surveillance (He et al, 2006), (Sun et al, 2011), precision agriculture (Burrell et al, 2004), (Tim et al, 2007), (Keshtgari and Deljoo, 2012), (Wu et al, 2015), disaster management (Ahmad et al, 2011), transportation systems (Katiyar et al, 2011), (Felemban and Sheikh, 2014), and others (Li and Xiong, 2013), (Mehdipour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Precision agriculture is a wealthy field of application for automated monitoring as it has been highlighted by both Srbinova et al [19] and Keshtgary and Delijoo [20] which have both developed WSN systems for improved quality in farming. They both followed the common WSN schema of nodes and base stations while showcasing efficient processes of gathering and distributing environmental parameters.…”
Section: Related Workmentioning
confidence: 99%